2012
DOI: 10.1021/jo301215d
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Trapping of a Cage Annulated Vinylidenecarbene and Approaches to Its Cycloalkyne Isomer

Abstract: A novel cage-annulated (bis-homocubyl) vinylidenecarbene has been generated and successfully trapped without any intermediacy of its cycloalkyne isomer. The greater kinetic and thermodynamic stability of the vinylidenecarbene vis-à-vis its cycloalkyne isomer has been predicted by DFT B3LYP/6-31G* calculations. The calculated results suggest the prospects of the cycloalkyne becoming amenable for trapping, if generated under suitable experimental conditions, owing to the substantial kinetic energy barrier associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The combined ltrates were concentrated in vacuo, then suspended in 10% aqueous sodium thiosulfate (185 mL) and stirred 1 h. The mixture was then extracted with diethyl ether (3 x 100 mL), and the combined organic phases were dried (Na 2 SO 4 ), ltered, and concentrated in vacuo to afford 7-norbornol (21) as an orange waxy solid (2.20 g, 98%): 1 7-norbornone (22): Following the procedure of Rosenkoetter et al, 49 to a suspension of pyridinium chlorochromate (5.39 g, 25 mmol) in dichloromethane (300 mL) was added a solution of 7-norbornol (21, 1.12 g, 10.0 mmol) in dichloromethane (150 mL). The reaction mixture was stirred until 7-norbornol (21) was completely consumed, as determined by GC-MS. Diethyl ether (150 mL) was then added and the mixture was stirred 30 min, then transferred to a separatory funnel and extracted with diethyl ether (150 mL). The organic phase was washed with water (3 x 400 mL), dried (Na 2 SO 4 ), ltered, and concentrated in vacuo.…”
Section: General Notesmentioning
confidence: 99%
See 3 more Smart Citations
“…The combined ltrates were concentrated in vacuo, then suspended in 10% aqueous sodium thiosulfate (185 mL) and stirred 1 h. The mixture was then extracted with diethyl ether (3 x 100 mL), and the combined organic phases were dried (Na 2 SO 4 ), ltered, and concentrated in vacuo to afford 7-norbornol (21) as an orange waxy solid (2.20 g, 98%): 1 7-norbornone (22): Following the procedure of Rosenkoetter et al, 49 to a suspension of pyridinium chlorochromate (5.39 g, 25 mmol) in dichloromethane (300 mL) was added a solution of 7-norbornol (21, 1.12 g, 10.0 mmol) in dichloromethane (150 mL). The reaction mixture was stirred until 7-norbornol (21) was completely consumed, as determined by GC-MS. Diethyl ether (150 mL) was then added and the mixture was stirred 30 min, then transferred to a separatory funnel and extracted with diethyl ether (150 mL). The organic phase was washed with water (3 x 400 mL), dried (Na 2 SO 4 ), ltered, and concentrated in vacuo.…”
Section: General Notesmentioning
confidence: 99%
“…10,2 The generation of alkynes via FBW rearrangements of alkylidene carbenes is generally considered to depend upon a thermodynamic equilibrium that favors the target alkyne over the corresponding carbene. [17][18][19][20][21] While this is the case for most monocyclic alkynes, 14,9,8 with the exceptions of cyclobutyne 17 and cycloheptyne, [22][23] the additional geometric constriction present in many polycyclic alkynes can potentially tip equilibrium in favor the carbene. In such cases, even direct synthesis of the strained alkyne will result in rearrangement to the alkylidene carbene through the reverse 1,2-shift, known as the Roger Brown rearrangement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alkylidenecarbenes ( 1 ), and surrogate carbenoids ( 2 ), often undergo 1,2-shifts to furnish alkynes ( 3 ) by a process commonly referred to as the Fritsch-Buttenberg-Wiechell (FBW) rearrangement (Scheme 1a) [1,2,3,4,5,6]. By extending this method to cyclic alkylidenecarbenes ( 4 ) and carbenoids ( 5 ), in which the formally sp 2 -hybridized carbon connected to the carbene center is part of a ring, strained cycloalkynes ( 6 ) have also been generated (Scheme 1b) [4,7,8,9]. In recent years, our laboratory has reported that cyclopropanated phenanthrene systems such as 7 [10,11,12,13] and 8 [14,15] can serve as photochemical precursors to 1 and 4 respectively (Scheme 2), and thus provide light-induced routes to the corresponding linear and cyclic alkynes.…”
Section: Introductionmentioning
confidence: 99%